Understanding the effect of a virtual moderator on people’s perception in remote discussion using social VR - Yang, Chi-Lan; Matsumoto, Keigo; Yu, Songping; Sawada, Leo; Arakawa, Kiyoaki; Yamada, Daisuke; Kuzuoka, Hideaki (Frontiers in Virtual Reality, 2023)
Social VR enables people to join a remote discussion by keeping a high social presence and physical proximity using embodied avatars. However, the missing nonverbal cues, such as mutual eye contact and nuanced facial expression, make it challenging for distributed members to manage turn-taking, which could lead to unequal participation and affect trust building. Therefore, we propose a virtual moderator to make distributed members feel included by seeing their nonverbal behavior. The virtual moderator was designed with a “prompt Q&A″ feature to enable users to share feedback and an “attention guidance” feature to encourage participation. The preliminary result of a controlled experiment in social VR with 30 participants showed that seeing the virtual moderator’s body orientation enhanced participants’ psychological safety. In contrast, the prompt Q&A feature enhanced the perceived co-presence of their remote counterparts. We discussed how nonverbal behavior could be designed using a virtual moderator to shape human perception of the group discussion in social VR. We also pointed out challenges when providing multiple supports simultaneously in social VR.